Sertula Florae Colombiae, XIV - Uribe Uribe Lorenzo (Caldasia)
Clidemia anoriensis L. Uribe, sp. n. / Miconia aguirrei L. Uribe, sp. n. / Huilaea macrocarpa ssp. minor L. Uribe, ssp. n. / Passiflora longipes Juss. var. oxyphylla L. Uribe, var. nov.